The role of dual bronchodilation in chronic obstructive pulmonary disease: an evidence-based review (Portuguese Journal of Family Medicine and General Practice, 2017)
Objective: Chronic obstructive pulmonary disease (COPD) affects 14.2% of the Portuguese population over 40 years of age. COPD is characterized by persistent airflow obstruction that is usually progressive, with significant impact on daily activities and quality of life. Exacerbations are associated with an accelerated decline in lung function and an increase in mortality. This review aims to evaluate the effectiveness of dual bronchodilation using anticholinergic and long-acting ß-agonist drugs in the treatment of COPD, compared with monotherapy, in terms of improvement in dyspnea, reduction of exacerbations, and improved quality of life. Data sources: MEDLINE, evidence-based medicine websites and bibliographic references of the selected articles were reviewed. Revision methods: A search of clinical guidelines, meta-analyses, systematic reviews and randomized clinical trials, published in the last 10 years, in English, Spanish and Portuguese was performed. The MeSH terms used were ‘Pulmonary disease, Chronic obstructive’, ‘Muscarinic antagonists’, ‘Receptors, Adrenergic, beta-2’, ‘Drug therapy, Combination’, and ‘Bronchodilator agents’. Results: Of the 145 articles found, five met the inclusion criteria for this review. One article reported the results of a clinical trial and four were guidelines. The clinical trial comparing dual bronchodilation (olodaterol plus tiotropium) with monotherapy with tiotropium found significant improvement in lung function in the first group, as well as improvement in clinical status, but this was not considered to be clinically relevant. The four guidelines claimed improvement in pulmonary function with use of dual bronchodilation. However, the clinical relevance of this benefit was not clear, in terms of reducing dyspnea, improving quality of life, and reducing the number of exacerbations. Conclusions: Dual bronchodilation improves lung function in patients with COPD, but the clinical benefit of this finding is not clear. Additional studies with similar methodology performed in relevant populations are needed to provide evidence for the beneficial effects of dual bronchodilation on patient-oriented outcomes.
Keywords: Pulmonary disease; Chronic obstructive; Muscarinic antagonists; Receptors; Adrenergic; beta-2; Drug therapy; Combination; Bronchodilator agents.